The x-intercept is when y=0 so substitute y=0 into the given equation and solve for x:

2x+3y=−9

2x+3(0)=−9

2x=−9

x=−4.5

Given equation. Substitute y=0. Simplify. Divide both sides by 2.

The x-intercept is then x=−4.5

The y-intercept is when x=0 so substitute x=0 into the given equation and solve for y:

2x+3y=-9

2(0)+3y=-9

3y=-9

y=-3

The y-intercept is then y=−3.

Plot the xx-intercept at −4.5 and the y-intercept at −3. Then draw a line passing through the intercepts to graph the line:

[Graph]

2x+3y=−9

2x+3(0)=−9

2x=−9

x=−4.5

Given equation. Substitute y=0. Simplify. Divide both sides by 2.

The x-intercept is then x=−4.5

The y-intercept is when x=0 so substitute x=0 into the given equation and solve for y:

2x+3y=-9

2(0)+3y=-9

3y=-9

y=-3

The y-intercept is then y=−3.

Plot the xx-intercept at −4.5 and the y-intercept at −3. Then draw a line passing through the intercepts to graph the line:

[Graph]